Effects of positive endomyocardial biopsy on the survival and the outcomes of catheter ablation of ventricular tachycardia in patients with cardiac sarcoidosis. (19th May 2022) - Dinov, B; Latuschynski, C; Ebbinghaus, H; Arya, A; Kuehl, M; Ueberham, L; Hindricks, G
Abstract: Funding Acknowledgements: Type of funding sources: Private hospital(s). Main funding source(s): Heart center of Leipzig Background: Cardiac sarcoidosis (CS) is frequently unrecognized cause of non-ischemic cardiomyopathy associated ventricular tachycardia (VT), who eventually require VT ablations because of refractory VTs; however, the reported long-term outcomes after VT ablation are conflicting. Because of the low diagnostic yield of the endomyocardial biopsy (EMB), diagnosis of CS is often based on clinical and imaging criteria, which can lead to misdiagnosing. Purpose and objectives: The purpose of this study was to identity whether patients with histologically-proven CS (EMB+) have different patient, procedural characteristics and outcomes after VT ablation as compared to those in whom the diagnosis was based on clinical criteria only (EMB-). Methods: Between 2015-2021, 153 patients with suspected CS were evaluated according to a specified protocol including CMR, 18FDG-PET, EMB, bronchoscopy and EBUS biopsy, and serum markers. Those who fulfilled the latest criteria for CS of the Japanese Circulation Society (JCS) were divided into 2 groups: EMB (+) CS proven by myocardial biopsy, and EMB (-) CS fulfilling the clinical criteria for CS. The following endpoints were defined: 1) VT recurrence after ablation; and 2) the composite endpoint of death, heart transplantation or LVAD implantation. Results: We identified 76 patients fulfilling the JCS criteria for CS (mean age 50 ± 10.6 years, 38% female, EMB (+) 35.5%). The leading symptoms were as follows: sustained VT in 23 (30%), high-grade AV block in 23 (30%), heart failure in 18 (24%), and other in 12 pts (16%). EMB (+) and the EMB (-) patients had similar clinical characteristics except for the imaging findings. EMB (+) patients exhibit LGE in CMR in 96% vs. 73% in EMB (-); P=0.024, whereas 18FDG-PET showed abnormal myocardial activity in 91% in the EMB (+) vs. 65% in the EMB (-); P=0.028. The primary composite endpoint was reached in 7.4% in EMB (+) group and in 12.2 % in EMB (-) group; P = 0.7. VT ablation was performed in 15 cases: 9 ablations (33%) in EMB (+) vs. 6 ablations (12%) in EMB (-); P=0.037. At the end of the procedure, all inducible VTs were successfully ablated in 100% of the EMB (-) patients vs. 56% in EMB (+) patients; P=0.1. VT recurrence was 78% in EMB (+) group vs. 67% in EMB (-); P = 0.6. The only procedural difference between the groups was the presence of vast RV low-voltage areas in 67% of the EMB (+) vs. 0% in EMB (-); P = 0.028. Conclusions: Patients with CS and positive EMB exhibit more often LGE in CMR, abnormal 18FDG-PET activity and required more frequently VT ablation. The procedural characteristics between both groups were similar, except for the frequently observed RV low-voltage areas in most EMB (+) patients, whereas the RV was not affected in any of the EMB (-) patients. In spite of these differences, the VT recurrence rates and the survival seemed not to be affected by the histological evidence of CS in EMB.